Coronavirus disease 2019 (COVID-19) and immune-mediated inflammatory rheumatic diseases: at the crossroads of thromboinflammation and autoimmunity - E. L. Nasonov; T. V. Beketova; T. M. Reshetnyak; A. M. Lila; L. P. Ananieva; T. A. Lisitsyna; S. K. Soloviev (Научно-практическая ревматология)
Inflammation and coagulation are key basic mechanism of protection against all potentially pathogenic mechanical and biological factors targeting human organism from inner and outer environment. On the other hand, uncontrolled inflammation results in hypercoagulation, inhibition of anticoagulation and alteration of mechanisms responsible for resolution of inflammation, while production of “procoagulant” mediators (thrombin, tissue factor and others), activation of platelets and of vascular endothelial cells maintains inflammation. All factors taken together serve as the basis for a pathological process called thromboinflammation or immunothrombosis. Currently thromboinflammation is considered in the broad sense as a universal pathogenetic mechanism of numerous widespread acute and chronic conditions, including immune-mediated (autoimmune) inflammatory rheumatic diseases, oftentimes complicated by severe irreversible damage to vital organs. Thromboinflammation gained specific attention during СОVID-19 (coronavirus disease 2019) pandemic, caused by SARS-Cov-2 (severe acute respiratory syndrome Coronavirus-2). COVID-19 is considered currently as systemic thromboinflammation syndrome, manifesting via generalized thrombosis of arterial and venous macro- and microvasculature, termed as COVID-19-coagulopathy. The paper discusses common pathogenetic coagulopathy mechanisms in COVID-19 and immune-mediated (autoimmune) inflammatory rheumatic diseases (IMRDs), associated with overproduction of antiphospholipid antibodies, activation of the complement system, and dis-regulated synthesis of proinflammatory cytokines, etc. Delineating the autoimmune subtype of thromboinflammation, identification of genetic (i.e., genes encoding the complement system and others) and molecular-biologic biomarkers associated with higher occurrence of COVID-19-coagulopathy are the most relevant undertakings for the current practice. Gaining insights into mechanisms of thromboinflammation and converting them into potential pharmacotherapies of IMDs would facilitate and accelerate the drafting of effective therapeutic strategies for COVID-19.